Design and simulation of high frequency colpitts oscillator based on BJT amplifier - Khalid A. Humood; Omar A. Imran; Adnan M. Taha (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Frequency oscillator is one of the basic devices that can be used in most electrical, electronics and communications circuits and systems. There are many types of oscillators depending on frequency range used in an application such as audio, radio and microwave. The needed was appeared to use high and very high frequencies to make the rapid development of advanced technology Colpitts oscillator is one of the most common types of oscillator, it can be used for radio frequency (RF), that its output signal is often utilized at the basic of a wireless communication system in most application. In this research, a Colpitts oscillator is comprised from a bipolar junction transistor (BJT) amplifier with LC tank. This design is carrying out with a known Barkhausen criterion for oscillation. Firstly, is carried out using theoretical calculation. The secondary is carried out using simulation (Multisim 13). All the obtained result from the above two approaches are 10 MHz and 9.745 MHz respectively. This result is seen to be very encouraging.